Diseño interior en el edificio palacio del corregidor en Sogamoso, Boyacá (2020)
The interior design project in the Palacio del Corregidor Building is located in the downtown sector of Sogamoso, Boyacá, one of the most symbolic buildings in the city, due to its historical, aesthetic and symbolic value, taking into account the theme of the project and the condition of the building as an asset of cultural interest for the region, the historical, urban, architectural and cultural aspect was related, which allowed us to approach the property and its current status. Once the diagnosis has been prepared, the criteria for intervention in the building are defined that guarantee physical permanence, preventive protection, improvement and sustainability, generating strategies to adopt maintenance procedures, redesigning new interior spaces for cultural use, preserving its image and characteristics of republican architecture. . Its state of intervention will be optimal for the promotion and dissemination of cultural and artistic values which will contribute to all ages and social classes, to the municipality, the department and the nation. This led us to redefine its interior space in its entirety, activating the environment and revitalizing new spaces to generate well-being, economy and cultural interest.